2004
DOI: 10.1177/1043986203262300
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Variations of Stressors Among Police Officers during an Era of Decreasing Crime

Abstract: The historic decrease in the crime rate reported within many U.S. cities during the past decade provides an opportunity to determine if police officers would rank other stressors higher when the ubiquitous crime factor is proportionally minimized. This study tests the assumption that law enforcement officers would experience lower levels of stress during an extended period of relatively low crime rates and predominantly report external, non-crime related factors as primary stressors. Stressor sources were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…interference with family life, excessive workload, uncivil interactions with coworkers; Adams & Buck, 2010;Collins & Gibbs, 2003;Davey, Obst, & Sheehan, 2001 2016; Morash, Kwak, & Haarr, 2006;Pasillas, Follette, & Perumean-Chaney, 2006) and in relation to their job duties (e.g. interactions with hostile suspects, offenders, and emotionally distraught victims; Anderson, Litzenberger, & Plecas, 2002;Garcia, Nesbary, & Gu, 2004). Among police officers, social stressors produced from civilian, suspect, co-worker, and supervisor interactions, have also been significantly related to reduced productivity, increased aggressiveness (Karaffa & Koch, 2016), turnover intention, psychological distress, and emotional exhaustion (Adams & Buck, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…interference with family life, excessive workload, uncivil interactions with coworkers; Adams & Buck, 2010;Collins & Gibbs, 2003;Davey, Obst, & Sheehan, 2001 2016; Morash, Kwak, & Haarr, 2006;Pasillas, Follette, & Perumean-Chaney, 2006) and in relation to their job duties (e.g. interactions with hostile suspects, offenders, and emotionally distraught victims; Anderson, Litzenberger, & Plecas, 2002;Garcia, Nesbary, & Gu, 2004). Among police officers, social stressors produced from civilian, suspect, co-worker, and supervisor interactions, have also been significantly related to reduced productivity, increased aggressiveness (Karaffa & Koch, 2016), turnover intention, psychological distress, and emotional exhaustion (Adams & Buck, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Our reasoning is in line with Laufersweiler-Dwyer and Dwyer's (2000) observation that police officers with experience levels of 6 to 10 years (called the disenchantment phase) report higher stressor scores. In addition, Garcia, Nesbary, and Gu (2004) report data suggesting a similar curvilinear relationship between job tenure and stress. Their study, also conducted among police officers, reveals that respondents with 5 to 10 years of job tenure report higher stressor scores.…”
Section: Analysesmentioning
confidence: 95%
“…Although several studies have detected the high risk police officers have for CVD (Franke et aI., 2010;Joseph et al, 2009;Ramey et al, 2(09), few studies have addressed the reasons for the increased risk. Those studies that have suggested, surprisingly, that CVD risk might correlate with factors emanating from within law enforcement organizations themselves (Garcia, Nesbary, & Gu, 2004;Gershon, Lin, & Li, 2002;Ramey, 2003;Ramey et al, 2(08). For example, one study linked officers' CVD risk to fatigue associated with shift work, barriers to controlling working hours, work-life imbalance, and continual exposure to stress (Puttonen, Harma, & Hublin, 2010).…”
Section: Applying Research To Practicementioning
confidence: 99%